2018
DOI: 10.2340/00015555-3017
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Psoriasis and Psoriatic Arthritis and Patient Perceptions of Severity in Sweden, Norway and Denmark: Results from the Nordic Patient Survey of Psoriasis and Psoriatic Arthritis

Abstract: Optimal clinical management of psoriasis and psoriatic arthritis (PsA) requires understanding of the impact on patients. The NORdic PAtient survey of Psoriasis and PsA (NORPAPP) aimed to obtain current data on disease prevalence and patient perceptions in Sweden, Denmark and Norway. Among 22,050 individuals questioned, the reported prevalence of psoriasis and/or PsA was 9.7% (5.7% physician-diagnosed plus 4.0% self-diagnosed only); prevalence was similar in Sweden (9.4%) and Denmark (9.2%) but significantly hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(38 citation statements)
references
References 21 publications
(28 reference statements)
4
33
0
1
Order By: Relevance
“…Population demographics have been reported previously . There were approximately equal proportions of males (48.9%) and females (51.1%), and just over half of the respondents were in the older age group (55.1% aged 45–74 vs 44.9% aged 18–44).…”
Section: Resultssupporting
confidence: 52%
See 2 more Smart Citations
“…Population demographics have been reported previously . There were approximately equal proportions of males (48.9%) and females (51.1%), and just over half of the respondents were in the older age group (55.1% aged 45–74 vs 44.9% aged 18–44).…”
Section: Resultssupporting
confidence: 52%
“…About three‐quarters of the respondents (74.6%) were diagnosed with PsO alone, and in the remaining quarter, respondents were diagnosed with PsA alone (15.1%) or PsA with PsO (10.3%). Most respondents (72.7%) with PsO alone considered their condition to be non‐severe; 26.9% considered their condition to be severe . Fewer respondents reporting PsA with or without PsO (PsA ± PsO) considered their condition to be non‐severe (38.9%); 58.7% considered their condition to be severe.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the Tromsø study, 10% of the participants reported ever experiencing psoriasis with a mainly mild course. It is well known that the Scandinavian region has one of the highest psoriasis prevalences in the world . In the following, our results will primarily be discussed in comparison with the results of Danielsen et al …”
Section: Discussionmentioning
confidence: 52%
“…The worldwide prevalence of psoriasis ranges between 0.09% and 11.9%, making psoriasis a substantial global problem. Psoriasis leads to disfiguration, disability and marked loss of productivity, according to the World Health Organization's global report on psoriasis .…”
mentioning
confidence: 99%